التدخل السلوكي لعلاج اضطراب طيف التوحد (ASD) إستراتيجية تحليل السلوك التطبيقي (ABA) أنموذجًا (Faculty of Education Scientific Journal, 2024)
Autism spectrum disorder is a complex developmental disability that affects children in their early childhood and is called; (Puzzle disorder) due to its complexity and ambiguity, it is a disability that has a comprehensive impact on all aspects of the child’s mental, social, emotional, motor and sensory development, and the most obvious deficiency aspects of this disability are the communication aspect and mutual social interaction. Applied behavior analysis is a new approach to improving behaviors and developing social skills, as applied behavior analysis comes as one of the best options available to deal with these abnormal behaviors within special abilities schools, in addition to its ability to effectively deal with undesirable behaviors by reducing, erasing, or replacing them with positive behaviors. The current research aims to identify the concept and characteristics of applied behavior analysis as a strategy for treating the autism spectrum, learn the basic steps and principles in applied behavior analysis, and reveal the procedures for forming new behaviors in the autistic child and ways to develop them. The research concluded with a number of results, the most important of which are: Applied behavior analysis is considered one of the behavior modification procedures and is among the effective modern therapeutic strategies for autistic children. It usually targets abnormal behaviors and seeks to change them and replace them with normal ones, and relies directly on objective observation of behavior. Applied behavior analysis procedures are among the successful methods that can be used with autistic children in learning various skills (independence, social, cognitive, perceptual, and motor) as well as solving behavioral problems that appear in the autistic child.
Keywords: Behavioral intervention; Applied behavior analysis; Autism spectrum disorder